1970
DOI: 10.3126/kumj.v8i2.3561
|View full text |Cite
|
Sign up to set email alerts
|

Post partum haemorrhage: Prevalence, morbidity and management pattern in Dhulikhel Hospital

Abstract: Background: Post partum haemorrhage (PPH) is the leading cause of maternal death worldwide. PPH occurs in up to 18% of total births. Among different factors, PPH due to uterine atony is the primary and direct cause of maternal mortality comprising about 90%. Objective: The objective of the present study was to assess the prevalence, morbidity and management pattern of PPH in Dhulikhel Hospital. Materials and methods: Hospital based retrospective study was carried out at Kathmandu University School of Medical S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Similar study done in Nepal revealed secondary PPH as the cause of about 32% cases of PPH. 5,12 Sixty eight percent of our patients had vaginal delivery, however it cannot be said that vaginal delivery predisposes to secondary PPH as the overall vaginal deliveries are more as compared to caesarean deliveries. Thirty six (72%) cases were referred from outside.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar study done in Nepal revealed secondary PPH as the cause of about 32% cases of PPH. 5,12 Sixty eight percent of our patients had vaginal delivery, however it cannot be said that vaginal delivery predisposes to secondary PPH as the overall vaginal deliveries are more as compared to caesarean deliveries. Thirty six (72%) cases were referred from outside.…”
Section: Discussionmentioning
confidence: 80%
“…Active management of third stage of labour has been followed as a strategy to prevent PPH including secondary PPH. 12 Prolonged third stage of labour has been shown to increase the risk of secondary PPH. 13 The observation that unbooked and unsupervised pregnancies coupled with unskilled deliveries or home deliveries lead to increased risk of both primary and secondary PPH has been well established.…”
Section: Discussionmentioning
confidence: 99%
“…of maternal deaths in developing countries [1]. According to WHO, there are about 14 million cases of obstetric haemorrhage each year [2].…”
Section: Introductionmentioning
confidence: 99%
“…7 But traumatic PPH in present study was most commonly present in women with single parity. Another study done by Singh et al also reported that most of the PPH cases were multiparas, poor, low socioeconomic class, were unbooked and were from the rural area.…”
Section: Discussionmentioning
confidence: 43%